Effect of a ketogenic diet, time-restricted eating, or alternate-day fasting on weight loss in adults with obesity: a randomized clinical trial - José Ignacio Martínez-Montoro; Borja Bandera; Mario Gutiérrez-Bedmar; Ana María Gómez-Pérez; Manuel Macías-González; Isabel Moreno-Indias; Francisco J. Tinahones (BMC Medicine)
Abstract Background Studies evaluating the effects of novel, alternative dietary approaches for weight loss compared with the Mediterranean diet (MedDiet) are lacking. We aimed to evaluate the effects of diets with varying ketogenic potential, i.e., a very-low carbohydrate diet (ketogenic diet, KD), time-restricted eating (TRE), and modified alternate-day fasting (mADF) on weight loss in obesity, compared with a MedDiet. Methods Three-month, parallel-arm, randomized clinical trial including 160 adults with obesity. Participants were randomized to 1 of 5 groups: control (MedDiet), KD, early TRE (eTRE), late TRE (lTRE), or mADF. All diets were calorie-restricted. The primary outcome was differences in weight loss from baseline to 3 months between a calorie-restricted MedDiet and each of the four remaining calorie-restricted dietary interventions. Secondary outcomes included change in body mass index, body composition, and cardiometabolic risk factors. Results The mean age was 45.7 years (SD 10.7), and 70.6% were women. One hundred forty participants completed the study. Significant differences in weight loss from baseline to 3 months were found between KD and the control group [− 3.78 kg (− 5.65 to − 1.91 kg)], between mADF and the control group [− 3.14 kg (− 4.98 to − 1.30 kg)], and between lTRE and the control group [− 2.27 kg (− 4.13 to − 0.40 kg)], but not between eTRE and the control group [− 1.22 kg (− 3.07 to 0.64 kg)]. Conclusions These results suggest that a calorie-restricted KD, mADF, or lTRE may be more effective for weight loss than a calorie-restricted MedDiet in obesity. Further research is needed to evaluate the long-term feasibility and efficacy of these dietary interventions compared with the MedDiet. Trial registration ClinicalTrials.gov (NCT04453150).